Transforming HR Creating value through people - Withers, Mark.; Williamson, Mark.; Reddington, Martin (Amsterdam ; Boston ; London : Butterworth-Heinemann, 2010)
"Transforming HR, Second edition offers robust, practical advice on changing the way human resource management is undertaken, walking you through the transformational process from initial planning to the evaluation of outcomes. Intended as an inspiring, hands-on guide to planning, implementing and evaluating transformation strategies, the book is an essential companion as you work to increase the value of HR in your organisation."--BOOK JACKET.
Previous ed.: Oxford: Elsevier Butterworth-Heinemann, 2005.
Includes bibliographical references and index.
All age.
Keywords: Personnel management